Support for Family Politics and Democracy: Evidence from Indonesia - Liddle, R. William; Mujani, Saiful; Irvani, Deni (UIN Syarif Hidayatullah Jakarta, 2022)
Abstract. Studies on the relationship between family politics and democracy are inconclusive. A number of studies suggest that family politics weakens democracy, and some other studies found that family politics does not matter to democracy, and some other works on the issue even reveals that family politics strenghthens democracy. This article is to report the result of a study about the relationships between family politics and democratic support and performance. Mass support for democracy is an indicator of democratic consolidation at the attitudinal level, and mass assessment of democratic performance is also crucial to the extent in which a democracy performs. In addition, this article addresses the issue how political knowledge of family politics predicts support for family politics. Lack of political knowledge among the massess in developing democracy is probably responsible for the support for family politics. This article relies on relevant data of a nation wide public opinion survey of the fourth largest electorate in the world, Indonesian voter. The findings of this study are: Indonesian voters are in general negative towards family politics; attitudes toward family politics do not matter to democratic support, but explain significantly assessment of democratic performance: negative attitude towards family politics decreases positive assessment of democratic performance. This pattern indicates a syndrome of critical citizens, i.e. political knowledge and education reject family politics which positively assesses democratic performance. Family politics does not demand a better democratic performance. Education does. Keywords: Democracy, Democratic Performance, Family Politics, Critical Citizen, Political Knowledge, Education, Indonesia. Abstrak. Studi tentang hubungan antara dinasti politik dan demokrasi sejauh ini menghasilkan kesimpulan yang belum konklusif. Sejumlah penelitian menunjukkan bahwa dinasti politik telah melemahkan demokrasi, tapi sebagian penelitian yang lain menyebut dinasti politik tidak masalah bagi demokrasi, bahkan memperkuat demokrasi itu sendiri. Artikel ini menampilkan hasil kajian tentang hubungan antara dinasti politik dengan dukungan dan kinerja demokrasi. Dukungan publik terhadap demokrasi merupakan indikator konsolidasi demokrasi pada level sikap, dan penilaian massa terhadap kinerja demokrasi juga penting untuk menguji sejauh mana demokrasi bekerja. Selain itu, artikel ini mengangkat isu bagaimana pengetahuan politik tentang dinasti politik memprediksi dukungan terhadap politik kekeluargaan. Kurangnya pengetahuan politik warga di negara demokrasi yang sedang berkembang menjelaskan mengapa warga mendukung dinasti politik. Artikel ini menggunakan data survei opini publik nasional di negara yang memiliki jumlah penduduk terbesar keempat di dunia, yakni Indonesia. Temuan dari penelitian ini adalah: Pemilih Indonesia secara umum bersikap negatif terhadap dinasti politik. Meskipun sikap publik terhadap dinasti politik secara umum tidak berhubungan dengan dukungan terhadap demokrasi pada tataran normatif, tapi ia menjelaskan secara signifikan penilaian publik atas kinerja demokrasi: sikap negatif terhadap dinasti politik terbukti menurunkan penilaian positif atas kinerja demokrasi. Pola ini menunjukkan sindrom warga kritis, di antaranya mereka yang memiliki pengetahuan politik dan pendidikan baik— cenderung menolak dinasti politik, dan karenanya positif dalam menilai kinerja demokrasi. Dinasti politik tidak menuntut kinerja demokrasi yang lebih baik. Pendidikan justru sebaliknya. Kata Kunci: Demokrasi, Kinerja Demokrasi, Dinasti Politik, Warga Kritis, Pengetahuan Politik, Pendidikan, Indonesia.